Doxycycline Interferes With Tau Aggregation and Reduces Its Neuronal Toxicity - Medina, Luciana; González-Lizárraga, Florencia; Dominguez-Meijide, Antonio; Ploper, Diego; Parrales, Valeria; Sequeira, Sabrina; Cima-Omori, Maria-Sol; Zweckstetter, Markus; Del Bel, Elaine; Michel, Patrick P.; Outeiro, Tiago Fleming; Raisman-Vozari, Rita; et al. (Frontiers in Aging Neuroscience, 2021)
Tauopathies are neurodegenerative disorders with increasing incidence and still without cure. The extensive time required for development and approval of novel therapeutics highlights the need for testing and repurposing known safe molecules. Since doxycycline impacts α-synuclein aggregation and toxicity, herein we tested its effect on tau. We found that doxycycline reduces amyloid aggregation of the 2N4R and K18 isoforms of tau protein in a dose-dependent manner. Furthermore, in a cell free system doxycycline also prevents tau seeding and in cell culture reduces toxicity of tau aggregates. Overall, our results expand the spectrum of action of doxycycline against aggregation-prone proteins, opening novel perspectives for its repurposing as a disease-modifying drug for tauopathies.